Characterizing hypoxia in human glioma: A simultaneous multimodal MRI and PET study. (14th August 2017) - Preibisch, Christine; Shi, Kuangyu; Kluge, Anne; Lukas, Mathias; Wiestler, Benedikt; Göttler, Jens; Gempt, Jens; Ringel, Florian; Al Jaberi, Mohamed; Schlegel, Jürgen; Meyer, Bernhard; Zimmer, Claus; et al.
Abstract : Hypoxia plays an important role for the prognosis and therapy response of cancer. Thus, hypoxia imaging would be a valuable tool for pre‐therapeutic assessment of tumor malignancy. However, there is no standard validated technique for clinical application available yet. Therefore, we performed a study in 12 patients with high‐grade glioma, where we directly compared the two currently most promising techniques, namely the MR‐based relative oxygen extraction fraction (MR‐rOEF) and the PET hypoxia marker H‐1‐(3‐[ 18 F]‐fluoro‐2‐hydroxypropyl)‐2‐nitroimidazole ([ 18 F]‐FMISO). MR‐rOEF was determined from separate measurements of T 2, T 2 * and relative cerebral blood volume (rCBV) employing a multi‐parametric approach for quantification of the blood‐oxygenation‐level‐dependent (BOLD) effect. With respect to [ 18 F]‐FMISO‐PET, besides the commonly used late uptake between 120 and 130 min ([ 18 F]‐FMISO120–130 min ), we also analyzed the hypoxia specific uptake rate [ 18 F]‐FMISO‐ k 3, as obtained by pharmacokinetic modeling of dynamic uptake data. Since pharmacokinetic modeling of partially acquired dynamic [ 18 F]‐FMISO data was sensitive to a low signal‐to‐noise‐ratio, analysis was restricted to high‐uptake tumor regions. Individual spatial analyses of deoxygenation and hypoxia‐related parameter maps revealed that high MR‐rOEF values clustered in (edematous) peritumoral tissue, while areas with high [ 18 F]‐FMISO120–130 min concentrated in and around active tumor with disrupted blood–brain barrier, i.e. contrast enhancement in T 1 ‐weighted MRI. Volume‐of‐interest‐based correlations between MR‐rOEF and [ 18 F]‐FMISO120–130 min as well as [ 18 F]‐FMISO‐ k 3, and voxel‐wise analyses in individual patients, yielded limited correlations, supporting the notion that [ 18 F]‐FMISO uptake, even after 2 h, might still be influenced by perfusion while [ 18 F]‐FMISO‐ k 3 was severely hampered by noise. According to these results, vascular deoxygenation, as measured by MR‐rOEF, and severe tissue hypoxia, as measured by [ 18 F]‐FMISO, show a poor spatial correspondence. Overall, the two methods appear to rather provide complementary than redundant information about high‐grade glioma biology. Abstract : Direct comparison of MR‐based relative oxygen extraction fraction (MR‐rOEF) with the PET hypoxia marker [ 18 F]‐FMISO was performed in 12 patients with glioblastoma. While high MR‐rOEF values clustered in (edematous) peritumoral tissue, [ 18 F]‐FMISO120–130min accumulated in and around active tumor with contrast enhancement in T 1 ‐weighted MRI. According to these results, vascular deoxygenation, as measured by MR‐rOEF, and severe tissue hypoxia, as measured by [ 18 F]‐FMISO, show a poor spatial correspondence, indicating that the two methods rather provide complementary information about high‐grade glioma biology.